Antifungal Activity of Derum (Juglans Regia L. Bark) Extracts Against Candida Albicans Isolates (In Vitro Study) (Mustansiria Dental Journal, 2018)
Background: Derum is a one of "chewing sticks" existing in nature, collected from stem bark of walnut tree (Juglan regia L.). In some countries used mainly by women as tools for cleaning teeth and as coloring material for cosmetic purpose.The objective of performed study was aimed at evaluating the antifungal potential of two extracts from Juglans regia (L.) bark (water and water-methanol) against pathogenic Candida albicans strains.Materials and methods: Different concentrations of derum extracts were prepared by (water and water-methanol) methods, swap of saliva were collected from volunteers of patient at dental hospital, from which candida albicans were isolated,purified and diagnosis according to morphological characteristic and biochemical test. In vitro; experiments were prepared to assess the effect of different type and concentrations of derum extracts on growth of candida albicans by agar diffusion methods in comparison with nystatin and amphotericin B.Results: The result showed, candida albicans isolates sensitive to both types of derum extracts, which improved, by inhibition growth of candida albicans and inhibition were increased with the increasing concentrations from 0.5% to 50%. Nystatin inhibition growth of candida albicans bettter than both types of derum extracts (water and alcohol) and amphotericin B; but Candida albicans  more sensitive to both types of derum extracts than amphotericin B.Conclusion: Candida albicans were sensitive to different concentrations of (water and water-methanol) extracts of derum.